Knowledge, Attitudes and Practice of Tehran Citizens regarding the Social Distancing rules and its Related Factors during the COVID-19 Pandemic - Hosseini, Jalil; Nematollahi, Shahrzad; Ebrahim Pour, Majid; Sadegh zadeh, Zahra; Shariatpanahi, Samira; Sheikh Milani, Arezoo (Archives of Men’s Health, 2020)
Background: Due to the importance of social distancing in reducing the risk of transmission in Covid-19, contributing factors on success or failure of these rules are still unknown in Iran. The purpose of this study was to determine the level of knowledge, attitude and practice of the public about this rule and its requirements during the Covid-19 pandemic. Methods: This cross-sectional study was performed on 400 citizens over 18 years of age in Tehran city. Knowledge, attitude and practice regarding social distancing were assessed using a questionnaire and collected using electronic method (online). Data were analyzed using STATA software version 14 and descriptive and analytical statistics. Results: 371 (response rate: 92.5%) residents completed the questionnaire. 24% (n=27) knew the social distancing well. The mean ± SD of attitude score was 2.4±4 and 72% of the respondents was against the recommendation to observe intelligent distance. The mean knowledge and attitude scores were slightly higher in men than in women (3.69 vs. 3.55 and 2.51 vs. 2.20, respectively), but the mean practice score was lower in men (3.44 vs. 3.77) and all were not statistically significant. Conclusion: The respondents’ knowledge of the rule of social distancing during the COVID-19 pandemic was good, although people do not have a positive attitude towards this law. Although in some cases, such as in-person shopping, it was necessary to comply with this law, in most cases, such as keeping a distance of at least 1.5 meters with other people, avoiding handshakes, kissing and traveling was observed by a small percentage of people.